Efectividad analgésica del etoricoxib comparado con ketorolaco/dexametasona en el control del dolor en la exodoncia compleja de terceras molares mandibulares en pacientes del Servicio de Cirugía Bucal y Maxilofacial de la Clínica Estomatológica Central de la Universidad Peruana Cayetano Heredia - Funes Rumiche, Italo Martín (2020)
Third molar surgeries produce an inflammatory response with acute pain and swelling as the main clinical manifestations. Therefore, it is important to administer an effective analgesic medication. This double-blind, randomized, controlled clinical study was conducted to compare the analgesic effectiveness of etoricoxib with ketorolac/dexamethasone in the control of postoperative pain in mandibular third molar surgeries. A total of 94 extractions were distributed in statistically comparable groups (Etoricoxib 120mg VO 30 minutes preoperatively n= 50 and Ketorolac 60mg / Dexamethasone 4mg IM 30 minutes preoperatively n= 44). According to the results of the trial, analyzing the results of the analytical medicine: SPID (intensity of pain), average of the VAS (Visual Analogue Scale), global evaluation of the response to treatment (EGART) (p>0.05), we can conclude that Etoricoxib 120 mg, a selective anti-inflammatory of COX-2, administered orally preoperatively is a medication with a great analgesic power comparable with ketorolac / dexamethasone intramuscular.